The predictive validity of PSU-GET and academic success of PSU graduate students at Prince of Songkla University, Hat Yai campus, and the problems faced by those repeatedly failing the test - Urarat Narongraj (Prince of Sonkla University, 2021)
Thesis (M.A., Applied Linguistics)--Prince of Songkla University, 2008